Islamisasi Sains Dalam Pandangan Al–Khawarizmi: Sebuah Kajian Teoritis - Ahmad Ahmad; Luthfiyah Luthfiyah (Journal on Education, 2024)
The goal of this research is to delve deeper into the Islamization of science according to the perspective of Al-Khawarizmi. The method used in this study is library research. Data collection is carried out by gathering data from various literature. In this research, primary data is obtained from literature discussing the Islamization of Science from the perspective of Al-Khawarizmi. Meanwhile, the secondary data consists of literature about Al-Khawarizmi and his works up to his contribution to the development of contemporary science. The results of this research indicate that Al-Khawarizmi, a prominent Muslim scientist from the Golden Age of Islam, has made significant contributions to the Islamization of Science through his works covering mathematics, astronomy, geography, and cartography. The concept of Islamization of Science introduced by Al-Khawarizmi still holds strong relevance in the modern context. Through his approach that integrates science with Islamic values, Al-Khawarizmi emphasizes the importance of using science for the welfare of humanity and developing rational scientific methods. Additionally, his works in astronomy, geography, and cartography have also influenced the development of science in the Islamic world and worldwide. Thus, Al-Khawarizmi's legacy in the Islamization of Science provides inspiration and guidance for modern scientists and thinkers in utilizing science to advance human welfare and build a better world.